Health Literacy and Self-Care Management in Community Health Facilities - Wilandika, Angga; Sanusi, Santy; Karomah, Arsyi (Journal of Nursing Science Update (JNSU), 2024)
The prevalence of hypertension highlights the need for patients to manage their blood pressure independently, which is linked to health literacy. However, the relationship between self-care management and health literacy requires empirical validation. This study investigates the correlation between health literacy and self-care management among hypertensive patients at public health facilities. The study used a cross-sectional design involving 81 hypertensive patients aged 18 and older, sampled from a health centre in Bandung Regency, Indonesia. Health literacy was assessed using a hypertension health literacy scale, and self-care management was evaluated with a 40-item questionnaire. Kendall's Tau b was used for inferential analysis to examine the relationship between health literacy and self-care management. The findings indicated a significant correlation between health literacy and self-care management (t = 0.342; p < 0.05), showing that individuals with higher health literacy manage their hypertension more effectively and achieve better blood pressure control. These results pertain only to a specific population, suggesting further research on health literacy and self-care management among hypertensive patients in various health facilities